The Influence of Organizational Culture and Work Motivation on Teacher Performance at the International Standard School, Amanatul Ummah Mojokerto - Siti Rofifah; Akhmad Sirojuddin; Muhammad Anas Ma`arif; Muhammad Mujtaba Mitra Zuana (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Organizational Culture in a school and Institution is highly reflected values and norms which is being the vision and mission of the institution in achieving its goals. The suitable culture in its application will have a positive impact on work motivation to improve teachers’ performance better. The good performances of Educators and education staff will make the achievement results in the organization increase. This analysis used the independent variable of culture organization and work motivation, and the independent variable is teacher performance. The sample in this study was the formal and informal teachers of MBI. In this study, the sample collection technique of the researcher used probability sampling in simple random sampling, and the data collection technique use questionnaire which was distributed directly to 60 respondents. The result of this study shows that organizational culture (X1) and work motivation (X2) have a positive and significant effect on teacher performance (Y) either partially or simultaneously. In the thin study, there is an effect between X1 and Y partially as seen from the t-test result that the t research is 2.655 > t table is 2.00247, for the effects is 54,5%. And there is an effect between X2 and Y partially as seen from the t-test result that the t research is 2,181 > t table 2,00247, for the effects is 44.7%. And find the result of the calculation of the effect simultaneously that is 96.8%.